Different cytokinin histidine kinase receptors regulate nodule initiation as well as later nodule developmental stages in Medicago truncatula. (28th July 2016) - Boivin, Stéphane; Kazmierczak, Théophile; Brault, Mathias; Wen, Jiangqi; Gamas, Pascal; Mysore, Kirankumar S.; Frugier, Florian
Abstract: Legume plants adapt to low nitrogen by developing an endosymbiosis with nitrogen‐fixing soil bacteria to form a new specific organ: the nitrogen‐fixing nodule. In the Medicago truncatula model legume, the MtCRE1 cytokinin receptor is essential for this symbiotic interaction. As three other putative CHASE‐domain containing histidine kinase (CHK) cytokinin receptors exist in M. truncatula, we determined their potential contribution to this symbiotic interaction. The four CHKs have extensive redundant expression patterns at early nodulation stages but diverge in differentiated nodules, even though MtCHK1/MtCRE1 has the strongest expression at all stages. Mutant and knock‐down analyses revealed that other CHKs than MtCHK1/CRE1 are positively involved in nodule initiation, which explains the delayed nodulation phenotype of the chk1/cre1 mutant. In addition, cre1 nodules exhibit an increased growth, whereas other chk mutants have no detectable phenotype, and the maintained nitrogen fixation capacity in cre1 requires other CHK genes. Interestingly, an AHK4/CRE1 genomic locus from the aposymbiotic Arabidopsis plant rescues nodule initiation but not the nitrogen fixation capacity. This indicates that different CHK cytokinin signalling pathways regulate not only nodule initiation but also later developmental stages, and that legume‐specific determinants encoded by the MtCRE1 gene are required for later nodulation stages than initiation. Abstract : Legume plants adapt to low nitrogen by developing an endosymbiosis with nitrogen‐fixing soil bacteria to form a new specific organ: the nitrogen‐fixing nodule. We show here in the Medicago truncatula model legume that besides the MtCRE1 cytokinin receptor that is essential for this symbiotic interaction, other CHASE‐domain containing histidine kinases are positively and redundantly required during nodule initiation and to determine the nodule nitrogen fixation capacity. An AHK4/CRE1 genomic locus from the aposymbiotic Arabidopsis plant rescues nodule initiation but not the nitrogen fixation capacity, suggesting that legume‐specific determinants encoded by the MtCRE1 gene are required for late nodulation stages but not initiation.